Simultaneous HPLC-ELSD determination of sugars and cyclitols in different parts of Phacelia tanacetifolia Benth. (October 2018) - Al-Suod, Hossam; Gadzała-Kopciuch, Renata; Buszewski, Bogusław
Abstract: Three cyclitols ( allo -inositol, scyllo -inositol and myo-inositol) and seven sugars (xylose, d -mannose, d -glucose, sucrose, D-(+)-turanose, D-(+)-melezitose monohydrate and D-(+)-raffinose pentahydrate) were determined in different morphological parts of lacy phacelia by high performance liquid chromatography-evaporative light scattering detector (HPLC-ELSD) method in 30 min. The applied analytical method is rapid, simple, sensitive, low cost, reliable and suitable for profiling of major sugars and cyclitols in Phacelia tanacetifolia Benth. (lacy phacelia) parts. Pressurized liquid extraction and solid phase extraction were used as extraction and purification methods. The obtained results showed significant differences in the quantities and distribution of cyclitols and sugars found in the investigated morphological parts. The quantities of the identified cyclitols in lacy phacelia ranged between 1.07 and 4.68 mg/g of dried plant, while for sugars in the range of 1.07–25.3 mg/g. However, flowers were richer in cyclitols and sugars compared to the seeds. Graphical abstract: Highlights: Lacy phacelia an important source of cyclitols & sugars. Extraction, important step for an efficient & economically convenient achievement. SPE a valuable technique for purification & pre-concentration of cyclitols & sugars. HPLC-ELSD as a rapid & sensitive technique for cyclitols & sugars quantification. The flowers, richest in sugars & cyclitols compared to other investigated parts.